Pengaruh Penggunaan Media Pembelajaran Berbantuan Video Lomba Debat terhadap Keterampilan Menulis Teks Debat - Mahmudah, Salsabilla; Tressyalina, Tressyalina (Lembaga Yasin AlSys, 2023)
This study has three objectives. First, to describe the skill level of writing debate texts of experimental class students using video-assisted learning media as text teaching materials for class X MAN 3 Padang City. Second, it describes the skill level of writing debate texts of control class students without using video-assisted learning media as a medium for learning debate texts for class X MAN 3 Padang City students. This type of research is quantitative, the method used is the experimental method. The data in this study are students' debate text writing skills based on the structure and language rules of the debate text. The data source used was the debate text of class X MAN 3 Padang City students with a total sample of 27 texts. The data collection technique used in this study was giving treatment to students in the control and experimental classes, giving performance tests to the control and experimental classes. There are three data analysis techniques in this study, namely (1) giving scores to the debate texts that have been written by students (2) recording the scores obtained by students (3) converting scores into values using formulas. Based on the analysis that has been done, it can be concluded that the video-assisted learning media of the debate competition has an effect on the debate writing skills of class X MAN 3 Padang City students.